The effects of task-based language teaching on EFL vocabulary learning for secondary in a high school in Kien Giang province - Nguyễn Thái Dương (Trường Đại học Trà Vinh, 2024)
The objective of this study is to investigate if task-based language teaching (TBLT) enhances EFL students' retention of vocabulary. Specifically, the study aims to evaluate the impact of TBLT on vocabulary learning in upper secondary students and explore their perspectives on the effects of TBLT on EFL vocabulary learning.